PROSEC - Uma solução para o controle de processos maliciosos na plataforma Android - (:unkn) unknown (Universidade Federal do Pampa, 2016)
With the increasing use of the Android operating system, mobile devices have been the target of several attacks. These attacks are mainly intended to capture user information people. While there are several applications that aim to provide security of the existence of anti-virus software available today, these applications do not perform an analysis at a low level in the system, thus leaving loopholes for applications that run at a lower those that antivirus layer has access can take control the device and capture personal information. The objective of this research is to propose and implement a tool that performs the analysis of processes on the device that has embedded the Android operating system. It was found that through the analysis and control of these processes is possible to increase system security for all applications that are running, whether on a higher layer or lower in the system can be captured and analyzed by the proposed tool.
Keywords: Android; Segurança de sistema.; Processos; System security; Process; CNPQ::ENGENHARIAS